Increase in the functional capacity and quality of life among stroke patients by family caregiver empowerment program based on adaptation model - Kelana Kusuma Dharma; Dedi Damhudi; Nelly Yardes; Suhana Haeriyanto (Elsevier, 2018)
Purpose: The family caregiver's role is an important influence factor of patient's adaptation behaviour and quality of life after stroke. The purpose of this research was to identify the effect of caregiver empowerment program based on the adaptation model (CEP-BAM) on functional capacity and quality of life of patients after stroke. Methods: This research was a quasi-experimental research with a pre- and post-test control group design. The total participants who completed the research were 80 patients and their families, 40 participants in the intervention group and 40 participants in the control group. We conducted home visits to perform the intervention. The measurement of functional capacity and quality of life performed four times (pre-test and three times post-test). Data analysis was performed using the repeated measurement ANOVA or general linear model repeated measure (GLM-RM). Results: This research proves a significant difference in functional capacity and quality of life between the two groups and between pre-test and sixth months after intervention (P < 0.05). The quality of life of the intervention group in the sixth month after intervention was better than that of the control group (33.40 ± 3.65 vs 30.60 ± 2.78) with a significant difference (P < 0.05). Conclusion: It is concluded that CEP-BAM effectively increased patients' functional capacity and quality of life after a stroke in the sixth month after intervention. Keywords: Adaptation, Psychological, Caregivers, Empowerment, Indonesia, Quality of life, Stroke